The Impact of Teachers’ Competence in Managing Instructional Models and Learning Media on Students’ Learning Outcomes: Evidence from Indonesian Senior High Schools - Imelda Wokas; Romi J. Mongdong; Viktory N. J. Rotty (JR Education, 2026)
This study investigates the impact of teachers’ competence in managing instructional models and learning media on students’ learning outcomes in a senior high school context. Employing a quantitative ex post facto design, the study involved 83 students selected through simple random sampling from a population of 483 students. Data on teachers’ competence in managing instructional models and learning media were collected using Likert-scale questionnaires, while students’ learning outcomes were obtained from academic report scores. Data were analyzed using multiple linear regression, preceded by classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The findings reveal that: (1) teachers’ competence in managing instructional models has a positive and significant effect on students’ learning outcomes (t = 6.179, p < 0.05); (2) competence in managing learning media also shows a positive and significant effect (t = 8.147, p < 0.05); and (3) both variables simultaneously influence learning outcomes significantly (F = 33.032, p < 0.05). The coefficient of determination (R² = 0.452) indicates that 45.2% of the variance in students’ learning outcomes is explained by these two variables. The study highlights the critical role of teachers’ pedagogical competence, particularly in instructional design and media integration, in improving student achievement. These findings suggest the need for continuous professional development programs focusing on innovative teaching models and effective use of learning media to enhance educational quality.